An Assimilation-Based Model for Preventing Religious Radicalism - Supriadi, Lalu (KALAM, 2019)
Religious radicalism is a serious problem faced by many countries in the world, including Indonesia. Various efforts have been made by authorities to prevent the emergence of religious radicalism. One model of the efforts for preventing religious radicalism is the assimilation-based model. The purpose of this study is to examine some factors triggering religious radicalism, and the application of the assimilation-based model for the prevention of religious radicalism in Lombok society. This research uses qualitative approach. The data are collected through observation, interview and documentation methods. These data are then analyzed by following Miles and Huberman’s suggestion, consisting of data reduction, presentation and verification. This research finds out that, firstly, the main factor causing religious radicalism is due to lack of education among people; a situation which makes these people easily compromise radical doctrines without further critical thoughts. Secondly, the application of religious radicalism prevention model has to be accompanied by government’s policies and civil’s participation in social, cultural, and economic empowerment. In addition, it is important to conduct religious activities that create good atmosphere for all parties in conflict. This research concludes that religious radicalism can be prevented by social assimilation.